Arising Problems in Managing Virtual Project: Research on International Virtual Project Team Leaders - Kukytė, Aistė (Jaunųjų mokslininkų darbai, 2021)
Although the prevalence of project teams in international organizations is growing rapidly, while influencing the governance of organizations at the global, regional, and local levels, the response of organizations to such changes has been slower, according to authors A. I. Mockaitis, L. Zander, and H. De Cieri (2018). Organizations need to look at virtual project team development opportunities, methods, tools to learn to work in a multicultural space. The uptake of improvement opportunities for organizations would have a positive impact on many aspects like competition, efficiency, and reputation. In this context, it is important to analyse and research the uniqueness of virtual project teams and the problems arising in the management of these teams, because in the international business environment, the operation of these teams is a necessary condition for business to operate effectively. The article analyses the emerging problems in virtual project team management in international companies. A theoretical overview of possible problems in managing virtual project teams is presented, the results of the performed qualitative research are presented. During the research, managers working in international companies who lead a virtual project team were interviewed using the qualitative research method. The study was conducted in 2019-2020 and involved 9 informants working in Lithuania, the United Kingdom, the United States, Bangladesh, France, Malaysia, and Poland. The results of the study revealed the opinion of virtual project team leaders how these teams differ from traditional teams. The results revealed problems that may arise in the management of virtual project teams, such as misunderstanding and ambiguity of transmitted information, lack of emotion, presence and loss of information, higher time costs for work tasks, different, culturally influenced work principles and etiquette, and loss of personal and work balance boundaries. These problems are addressed in several ways, openly throughout the group, individually or through an external team.